Community-Oriented Parenting Culture Framework For Early Childhood Education in Indonesia: A Systematic Literature Review - Farny Sutriany Jafar; M Syarif Sumantri; Nurbiana Dhieni; Fachrul Rozie (Universitas Panca Sakti Bekasi, 2024)
This study contributes to the conceptualization of community-oriented parenting towards the context of early childhood education in Indonesia. It was based on a literature analysis of multicultural community care practices as a characteristic of Indonesia. The research design used a systematic literature review which selected 136 articles for analysis using a thematic approach. The theme narrated was how to describe the process of community care culture as identity and negotiation of community care culture within the ethno-parenting framework in early childhood education. This research proposed that the definition of parenting in Indonesian society could be used as material for the development of sustainable parenting education, especially the dimensions of ethno-parenting and multicultural education.